Would a Reasonable Person Now Accept the 1968 Harvard Brain Death Report? A Short History of Brain Death. (25th December 2018) - Veatch, Robert M.
Abstract: When The Ad Hoc Committee of Harvard Medical School to Examine the Definition of Brain Death began meeting in 1967, I was a graduate student, with committee member Ralph Potter and committee chair Henry Beecher as my mentors. The question of when to stop life support on a severely compromised patient was not clearly differentiated from the question of when someone was dead. A serious clinical problem arose when physicians realized that a patient's condition was hopeless but life support perpetuated body function. Thus, the committee stated that its first purpose was to deal with the burdens on patients and families as well as on hospitals and on patients needing hospital beds occupied by comatose patients. They intuited the strategy of "defining" these patients as dead, thus legitimating treatment stoppage. They noted that this would also serve a second purpose. Although the dead donor rule had not yet been clearly articulated, they claimed that defining patients as dead would also address controversy over obtaining organs for transplant . My mentors' discussions related to my interest in the intersection between questions primarily of medical fact (When has a human brain irreversibly ceased functioning?) and nonmedical questions of social policy (Should we treat individuals with dead brains and beating hearts as dead humans?). It quickly became clear that most committee members did not appreciate the interplay of these questions .